Application of water-soluble polymer inhibitor in metal corrosion protection: Progress and challenges - Yihang, Zhang (Frontiers in Energy Research, 2022)
The use of corrosion inhibitors can effectively avoid the corrosion of metals and alloys, but the conventional organic/inorganic corrosion inhibitors have certain toxic and side effects and environmental pollution problems (including some expensive toxic reagents and catalysts), prompting researchers to turn their attention to the research of water-soluble polymer corrosion inhibitors with green environment friendly and low pollution. This paper reviews the action mechanism of polymer inhibitors, the research status of natural polymer inhibitors (chitosan-based inhibitors, cellulose and its derivatives inhibitors, other carbohydrate inhibitors, protein inhibitors) and synthetic polymer inhibitors (epoxy resin inhibitors, polyethylene glycol inhibitors, conductive polymer inhibitors), The purpose is to provide some reference for the development of eco-friendly metal coatings.